Fatal Acute Pneumocephalus after Bilateral Drainage for Chronic Subdural Hematomas: Case Report - Lepić, Milan; Mandić-Rajčević, Stefan; Pavlićević, Goran; Benović, Radomir; Novaković, Nenad; Rasulić, Lukas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Pneumocephalus is a well-known complication in the surgical treatment of chronic subdural hematomas; however, its influence remains controversial. The amount of subdural air may vary, and it may cause worsening of symptoms, increase reoccurrence rates, and worsen the outcomes. Lethal outcome following acute onset of massive pneumocephalus was not previously reported.Case Report An 81-year-old man with bilateral hematomas underwent surgery under local anesthesia. Both hematomas were approached in the same surgery, and the drains were placed subdurally. After initial improvement, severe hypertension developed, followed by vital function and neurologic deterioration. Massive pneumocephalus with subarachnoid and contralateral intracerebral hemorrhage was revealed, causing a severe midsagittal shift. Emergency irrigation to evacuate subdural air was performed. However, there was no improvement. Further computed tomography confirmed subdural air collection, but it also revealed hemorrhage progression and intraventricular propagation. No further surgery was indicated.Conclusion Pneumocephalus is an underestimated but potentially devastating complication. Both intraoperative avoidance and postoperative prevention should be utilized to avoid subdural air ingress, and thus evade potentially fatal complications.
Keywords: chronic subdural hematoma; pneumocephalus; lethal complication; case report